Gasification Processes : Modeling and Simulation. - Nikrityuk, Petr A. (Wiley, 2014)
1.3 Benchmark Tests for CFD Modeling; 1.3.1 British Coal Utilization Research Association Reactor (BCURA); 1.3.2 Brigham Young University Reactor (BYU); 1.3.3 Pressurized Entrained-Flow Reactor (PEFR); References; Chapter 2 Gasification of Solids: Past, Present, and Future; 2.1 Introduction; 2.2 Historical Background; 2.3 Types of Gasification Reactors; 2.4 Trends in Gasifier Development; 2.5 Derived Challenges for Research; References; Chapter 3 Modeling of Moving Particles: Review of Basic Concepts and Models; 3.1 Introduction; 3.2 Soft-Sphere Model; 3.2.1 Numerical Implementation.